Transformasi Keterampilan Berbicara Melalui Multiliterasi di Era Digital - Suhartina, Suhartina; Oktavia, Silvin Pancarina (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2025)
This article aims to analyze the role of multiliteracies-based pedagogy in enhancing students' speaking skills in the context of 21st-century education. The study is driven by the increasing demands of communication across digital media and global settings, which require students to possess adaptive, multimodal, and context-aware speaking competencies. Employing a qualitative descriptive literature review method, this research synthesizes findings from 26 relevant national and international scholarly articles that explore the intersection of speaking skills and multiliteracy approaches. The analysis reveals that multiliteracy strategies—such as digital storytelling, telecollaboration, podcasting, digital comics, and virtual reality—significantly improve students' verbal fluency, confidence, and expressiveness in diverse learning environments. These approaches also benefit students with special educational needs and foster inclusive, culturally responsive communication practices. However, the implementation of multiliteracies in classrooms is still challenged by limited digital infrastructure, insufficient teacher training in media-integrated instructional design, and unequal access to educational technology. In light of these challenges, this study recommends systemic support through teacher professional development, broader access to digital learning tools, and curriculum reform that accommodates flexible, learner-centered, and media-rich instructional models. The integration of multiliteracies into mainstream education is expected to cultivate a generation of learners who are capable of speaking effectively, critically, and creatively across platforms and in various global contexts.